Design Thinking for Continuous Improvement in Applied Engineering Courses: Design Thinking untuk Perbaikan Berkelanjutan pada Mata Kuliah Teknik Terapan - Nindiani, Aina; Waluya, Aris Insan; Pratiwi, Annisa Indah (Indonesian Journal of Innovation Studies, 2026)
General Background: Higher education learning systems require continuous improvement to ensure learning quality, student participation, and satisfactory academic outcomes. Specific Background: In an applied engineering course at a higher education institution in West Java, student attendance averaged 74.45 percent per meeting and was associated with incomplete learning experiences and repeat rates. Knowledge Gap: Prior studies predominantly evaluated learning methods or attendance outcomes without systematically designing learning innovations grounded in student needs and experiential data. Aims: This study aims to apply design thinking as a structured framework to identify attendance-related barriers and enablers and to formulate learning system innovations in an applied engineering course. Results: Findings indicate strong student preferences for offline lectures and simulation-based learning, while attendance is primarily enabled by interesting lecture materials and constrained by work obligations. Significant relationships were identified between age and selected learning formats, as well as between gender and specific assessment types. Incremental innovations such as flipped classrooms and guest lectures, alongside radical innovations including experiential learning and AI-based learning platforms, were formulated through the ideate phase. Novelty: This study frames student attendance and learning quality as a design challenge and empirically integrates attendance data, student preferences, and structured innovation using design thinking. Implications: The results provide a data-driven framework for lecturers and academic managers to redesign applied engineering learning systems through continuous improvement grounded in participation behavior and student-centered innovation. Highlights • Student attendance reflects learning system configuration.• Design thinking structures learning innovation based on empirical data.• Continuous improvement aligns learning design with student needs. Keywords Design Thinking; Continuous Improvement; Applied Engineering Education; Learning System Design; Student Attendance